INCLUSIVE CHEMICAL CHARACTERIZATION OF TOURMALINE: MöSSBAUER STUDY OF FE VALENCE AND SITE OCCUPANCY - Dyar M.D.; Taylor M.E.; Lutz T.M.; Francis C.A.; Guidotti C.V.; Wise M. (My University, 1998)
We report here the results of a series of inclusive chemical characterizations, including all elements except oxygen, for a suite of 54 tourmaline samples. A combination of analytical techniques was used to analyze for major and light elements (electron microprobe), Fe 31 (Mossbauer spectroscopy), H (U extraction), and B, Li, and F (ion microprobe, or SIMS). The B content of the tourmalines studied ranges from 2.86 to 3.26 B per formula unit (pfu) with 31 anions; excess boron is believed to reside in the Si site. Li ranges from 0.0 to 1.44 Li pfu and F contents are 0.0-0.91 pfu. H contents range from nearly anhydrous up to 3.76 H pfu and do not correlate simply with Fe 31 content. Mossbauer results show that tourmaline exhibits the entire range of Fe 31 /SFe from 0.0-1.0. Fe 21 is represented in the spectra by three doublets, with occupancy in at least three distinct types of Y sites (with different types of nearest and next nearest neighbors). Fe 31 was found in 26 of the 54 samples studied. Although Mossbauer data do not allow the distinction between (Y) Fe 31 and (Z) Fe 31 site occupancies to be made, XRD data on these samples suggest that the majority of Fe 31 is also in Y. Of the samples studied, (4) Fe 31 occurs in nine; five of those were either olenite or uvite with extensive Na substitution. A mixed valence doublet corresponding to delocalized electrons shared between adjacent octahedra was observed in 14 of the samples studied. Projection pursuit regression analysis shows that distribution of Fe among doublets is a function (albeit a complex one) of bulk composition of the tourmaline and supports the interpretation of doublets representing different populations of neighbors.